Correlation of core strength and agility in badminton players - Nitin Savla, H.; Sangaonkar, M.; Palekar, T. (International Journal of Applied Research, 2020)
Background: Badminton is racquet sport played using racquets to hit a shuttlecock across a net. The important factors for badminton players are muscle strength, muscular endurance, power, speed, agility, flexibility, balance and coordination. The core muscles strength help to improve muscle coordinator between upper and lower extremities as well as reducing injury risk and improving performance. Agility is required in required in badminton as it is characterized by changing actions of short period and high or intensity coupled with a short resting time. As core strength and agility has an equal importance among the players which has an impact on the players performance. Aim: To find out the correlation of core strength and agility in badminton players. Method: A total of 30 sub elite badminton players were selected considering their no. of hours of playing badminton daily and no. of years of playing badminton. The players were evaluated for the core strength test - ventral, left lateral, right lateral, and dorsal and illionis agility test. The relation between the core strength and agility were evaluated by correlation analysis. The individual core strength test was correlated with the illionis agility test. Results: The result showed the correlation of core strength and agility. The result showed that there is a perfect negative correlation between core strength and agility in relation to time as the r values of ventral core strength test, left and right lateral core strength test and dorsal core strength test with agility are -0.64, -0.67, -0.67, and -0.58 respectively. Conclusion: This study suggests that there is a correlation seen between the core strength and agility in badminton players.